Carrot or stick? A study on “bid-rigging norms” by simulation: inducing factors and deterring measures - Morofuji, Hideyuki; Kurahashi, Setsuya (Frontiers in Applied Mathematics and Statistics, 2023)
In this study, we apply Axelrod's norms game model to construct a bid-rigging norms model. We show that the auction system primarily used in public procurements has a structure that induces bid-rigging; although Axelrod pointed out the need for meta-norms in establishing social norms, meta-norms are unnecessary for establishing bid-rigging norms. We also show that enforcement as a punishment for deviation from bid-rigging plays a critical role in establishing and maintaining bid-rigging. Using this model, we conduct an agent-based simulation to explore the authority's measures to deter bid-rigging by examining three measures: the flexible setting of reserve prices, the administrative surcharge and leniency system under the Antimonopoly Law, and applying the bid-rigging offense under the Criminal Law. As a result, we clarify that the administrative surcharge and leniency system under the Antimonopoly Law are insufficient to deter bid-rigging and that the flexible setting of reserve prices and applying the bid-rigging offense under the Criminal Law are effective. Furthermore, the study reveals that the simultaneous implementation of these three measures can effectively deter bid-rigging by reducing the bid-rigging offense under the Criminal Law to the administrative penalty level while increasing the effectiveness of the administrative surcharge and leniency systems under the Antitrust Law. However, note that this implementation requires the flexible setting of reserve prices and gives bidders more payoff.